ZNF703 is an important player in head and neck cancer. (23rd October 2019) - Orhan, Ceren; Bakır, Burak; Dalay, Nejat; Buyru, Nur
Abstract: Objectives: Despite advances in treatment, head and neck squamous cell carcinoma (HNSCC) remains difficult to treat and the overall survival rate has only modestly improved over the past years. Therefore, there is a need to understand the molecular mechanism of HNSCC. Zinc finger protein 703 (ZNF703) is an oncogenic transcription factor, and ZNF703 gene expression is altered in many cancers as a result of chromosome 8p12 amplification. The purpose of this study was to investigate the expression pattern of ZNF703 in HNSCC in association with CCND1 expression and Akt phosphorylation. Design: Prospective study. Setting: University hospital. Participants: One hundred and five patients with HNSCC. Methods: Fifty HNSCC tumour and non‐cancerous tissue samples were investigated by qRT‐PCR and Western blotting. Results: ZNF703 gene expression was increased in 22.9% of tumour tissues compared with its normal counterparts. The results were correlated with clinicopathological features, copy number variation and survival data. Conclusion: ZNF703 over‐expression is associated with copy number variation and this over‐expression may activate PI3K/Akt signalling pathway in HNSCC.